Geoelectrical Signatures of Reactive Mixing: A Theoretical Assessment - U. Ghosh; T. L. Borgne; D. Jougnot; N. Linde; Y. Méheust (Geophysical Research Letters)
Abstract Characterizing the effects of subsurface fluid mixing on biogeochemical reactions is a key step toward monitoring and understanding a range of processes and applications in which fluids of different chemical compositions mix, such as aquifer remediation, CO2 sequestration, or groundwater‐surface water interactions. Yet the development of noninvasive methods to monitor mixing processes remains an outstanding challenge. Mixing processes are controlled by concentration gradients that develop at scales below the spatial resolution of hydrogeophysical imaging techniques. To overcome this difficulty, we propose to focus on the geoelectrical response of mixing‐driven chemical reactions, for which the products are electrically more conductive than the background solution. For such reactions, we investigate the impact of reactive mixing on the resulting effective electrical conductivity. The transport equations are solved using the Lamellar Mixing Theory for a range of velocity gradients representative of the stretching rates experienced by mixing fronts in heterogeneous porous media. Focusing on simple shear flows, we demonstrate that such reactions may result in substantial changes (several orders of magnitude) in the effective conductivity over time, thus providing geoelectrical signatures of reactive mixing dynamics. The temporal evolution of the effective conductivity depends on the relative orientations of the applied electrical potential gradient, mean flow, and velocity gradient, yielding different sensitivities to dispersion processes, stretching rates, and reaction kinetics. These results suggest that the use of chemical reactions with electrically conductive products could help to overcome present limitations of time‐lapse geophysical imaging in the monitoring of the spatiotemporal dynamics of subsurface reactive mixing processes.